Pengaruh Sifat Alir dan Kompresibilitas terhadap Kualitas Tablet Loratadin ODT - Ramadhani, Dalifa; Zakiyah Darajat, Nur (Faculty of Pharmacy, University of Jember, 2026)
Tablet formulation quality is strongly influenced by manufacturing methods and powder characteristics, particularly flowability and compressibility. This study aimed to evaluate the physical properties of powder and tablet quality of loratadine orally disintegrating tablets (ODT) prepared by the direct compression method. The study was conducted using an experimental laboratory approach, where the powder mixture was evaluated for angle of repose, flow properties, and compressibility, followed by evaluation of tablet characteristics including weight uniformity, size uniformity, hardness, friability, and disintegration time in accordance with pharmacopeial standards. The results showed that the powder exhibited excellent flow properties with an angle of repose of 16.3°, indicating optimal flowability. The tablets met the requirements for size uniformity, friability (0.08%), and disintegration time (1.18–1.23 minutes), demonstrating good mechanical resistance and rapid disintegration suitable for ODT formulations. However, weight uniformity and hardness (2–2.8 kp) did not meet the required standards, indicating suboptimal compaction and powder distribution. These findings suggest that although direct compression is a simple and efficient method for ODT formulation, optimization of formulation components and process parameters, particularly mixing homogeneity, excipient composition, and compression force, is necessary to achieve consistent tablet quality.